2007
DOI: 10.1016/j.mce.2007.02.009
|View full text |Cite
|
Sign up to set email alerts
|

A role of FRK in regulation of embryonal pancreatic beta cell formation

Abstract: To cite this version:Björn Åkerblom, Cecilia Annerén, Michael Welsh. A role of frk in regulation of embryonal pancreatic beta cell formation. Molecular and Cellular Endocrinology, Elsevier, 2007, 270 (1-2) This is a PDF file of an unedited manuscript that has been accepted for publication. As a service to our customers we are providing this early version of the manuscript. The manuscript will undergo copyediting, typesetting, and review of the resulting proof before it is published in its final form. Please no… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
12
0

Year Published

2008
2008
2016
2016

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 14 publications
(14 citation statements)
references
References 14 publications
1
12
0
Order By: Relevance
“…Whilst i.v. administration into the tail vein is occasionally used for GTT tests (Akerblom et al 2007), it is more frequently used when experimental animals are implanted with intravenous catheters, usually for sampling purposes. In animals in which intravenous catheters are implanted, i.v.…”
Section: Route and Dose Of Glucose Administrationmentioning
confidence: 99%
“…Whilst i.v. administration into the tail vein is occasionally used for GTT tests (Akerblom et al 2007), it is more frequently used when experimental animals are implanted with intravenous catheters, usually for sampling purposes. In animals in which intravenous catheters are implanted, i.v.…”
Section: Route and Dose Of Glucose Administrationmentioning
confidence: 99%
“…β-TC-6 cells were cultured in serum-free medium for 48 h followed by 24 h in the presence or absence of GDNF and assessed for proliferation by staining for the proliferation marker Ki67 17 . GDNF increased the number of Ki67 positive cells in a dose dependent fashion (Fig.…”
Section: Gdnf Promotes β-Cell Survival and Proliferation In Vitromentioning
confidence: 99%
“…The role of Fyn in pancreatic ␤-cells is currently unknown; however, the related kinase YES has been shown to be required for granule mobilization/replenishment, and F-actin remodeling in sustained insulin secretion (63) and Fyn-related kinase FRK influences ␤-cell number during embryogenesis and neonatal life (64). In this study, we have shown that Fyn is also responsible for Kirrel2 phosphorylation in pancreatic ␤-cells.…”
Section: Discussionmentioning
confidence: 64%